EFFECTIVENESS WHOLE CELL VACCINE Edwardsiella ictaluri WITH DIFFERENT DOSAGE AND METHODS FOR PROTECTING SIAMESE CATFISH (Pangasianodon hypophthalmus) AGAINST EDWARDSIELLOSIS DISEASE - Listia, Octa; Setyawan, Agus; Kholidin, Edy Barkat (e-Jurnal Rekayasa dan Teknologi Budidaya Perairan, 2022)
One of major problem of siamse catfish (Pangasianodon hypophthalmus) culture is Edwardsiliosis bacterial disease of Edwardsiella ictaluri, causes economic losses because it causes high mortality and reduces the quality of fishery products. Currently, the use of antibiotics as an effort to control the disease has been prohibited due to the impact of residual hazards, resistance and decreased food safety value. Therefore we need an alternative solution that is effective, efficient and applicable through the vaccines application. The aim of this research was to analyze the effectiveness of the Whole cell Edwardsiella ictaluri vaccine with different doses and different application methods to protect Siamese catfish (Pangasianodon hypophthalmus) from Edwardsiellosis disease. The research was conducted using a completely randomized design (CRD) method consisting of 3 methods, namely oral vaccine, immersion vaccine, and injection vaccine. Each method consisted of 4 different dose treatments with 3 replications. The results showed that the vaccine application using different methods resulted in different survival rates, relative survival rates, specific growth rates and mean time to death. The oral vaccine method using each different dose resulted in the best survival rate, relative survival percentage, and mean time to death. The immersion vaccine method with a dose of 10.9 resulted in the highest specific growth rate.